The role of phenols in the influence of herbal extracts from Salvia officinalis L. and Matricaria chamomilla L. on two-spotted spider mite Tetranychus urticae Koch - Tomczyk, Anna; Suszko, Magdalena (Biological Letters, 2012)
Extracts prepared from 2 medicinal herbs (common sage Salvia officinalis L. and German chamomile Matricaria chamomilla L.) were used in this study for biological control of spider mites. Their effect on mortality, fecundity, and development of Tetranychus urticae Koch on English ivy (Hedera helix L.) was studied under laboratory and greenhouse conditions. The extracts were prepared by soaking fresh Salvia leaves or dry Matricaria flowers in ethanol for 24 h, followed by evaporation, and finally suspension of the pellets in water. Full extracts and extracts without phenols were tested. The Salvia extracts had a higher acaricidal activity than Matricaria extracts, but the toxicity of both extracts to spider mite eggs was low. The toxic effect of full Salvia extracts on larval stages and females of T. urticae was evident. More than 50% of larvae and females were killed by this treatment in 4 days. Besides, total fecundity of survived females was evidently lower. Mortality and low fecundity after full Salvia extract application decreased the spider mite population by 76%. The toxicity of Salvia extracts after removal of phenols strongly declined, so the negative effect of the full Salvia extract on spider mites was connected with a high concentration of phenolic compounds. The toxic effect of Matricaria extracts in all tests was much lower and no evident role of phenolic compounds in its extracts was observed.